(untitled) (The Research of Medical Science Review, 2025)
Background: Low Back Pain (LBP) Is A Prevalent Global Health Issue, Affecting Individuals of All Ages. It Is Defined by The Location of Pain Typically Between the Lower Ribs’ Margins and Buttocks Creases. Among University Students, It Is Alarmingly Common Due to Factors Such as Sedentary Behavior, Poor Posture, And Academic Stress. LBP Has a Significant Impact on Students of Life Sleep. This Study Aims to Explore the Prevalence of LBP and Its Association with Sleep Quality Among University Students. Objective: The Primary Objective of This Study Was to Estimate the Prevalence of LBP And Examine Its Relationship with Sleep Quality Among Undergraduate Students in The Allied Health Sciences Department at Iqra National University, Peshawar. Methods: A Cross-Sectional Study Was Conducted With 330 Participants Aged 18-30 Years. The Sample Was Selected Using a Convenience Sampling Technique. Participants Completed a Demographic Questionnaire, The Pittsburgh Sleep Quality Index (PSQI), And Other Relevant Measures. Data Were Collected and Analyzed Using SPSS Software, With Both Quantitative and Qualitative Analyses Performed. Results: The Study Found That 88.4% Of Students Reported Experiencing LBP, With Males Experiencing Higher Rates. A Significant Proportion (70.6%) Of Students Reported Minimal to Moderate Sleep Disturbances. Sleep Quality Was Poor for Many, with 38.5% Rating Their Sleep as Fairly Good And 17.9% Rating It as Very Bad. A Strong Correlation Was Found Between Poor Sleep Quality and The Prevalence Of LBP Conclusion: This Study Highlights a High Prevalence of LBP Among University Students, With Poor Sleep Quality Significantly Contributing to The Condition. The Findings Suggest That Sedentary Behavior, Poor Posture, And Stress Are Key Factors. Interventions Targeting Ergonomic Improvements, Physical Activity, And Better Sleep Quality Could Help Reduce the Burden of LBP In Academic Settings.